2007
DOI: 10.1080/15412550701603775
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Apoptosis in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a highly prevalent airway disease characterized by an abnormal inflammatory response of the lungs to noxious particles and gases. Cigarette smoking remains a major risk factor in COPD development. Accumulating evidence suggests that apoptosis, a regulated form of cell death, may play an important role in COPD pathogenesis. Increased numbers of apoptotic cells can be detected in lung tissue and airways of human subjects with COPD, relative to normal lungs or those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 56 publications
1
68
0
1
Order By: Relevance
“…A-aDO 2 should be increased proportionally by the reduced surface and integrity of AECs. Recently, injury of AECs has been of great concern as the primary pathogenesis of smoking-induced PE (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)31,35,36). A recent ultrastructural study showed early disruption of AECs to be associated with smoking-induced chronic inflammatory processes and regional hypoxia (1,3,31).…”
Section: Rgbmentioning
confidence: 99%
See 1 more Smart Citation
“…A-aDO 2 should be increased proportionally by the reduced surface and integrity of AECs. Recently, injury of AECs has been of great concern as the primary pathogenesis of smoking-induced PE (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)31,35,36). A recent ultrastructural study showed early disruption of AECs to be associated with smoking-induced chronic inflammatory processes and regional hypoxia (1,3,31).…”
Section: Rgbmentioning
confidence: 99%
“…Injury of alveolar endothelial cells (AECs) is of great concern and has been considered the primary pathogenesis of PE (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Several histopathologic studies have shown early damage of these cells in smokers and mild-PE patients (2)(3)(4)(8)(9)(10).…”
mentioning
confidence: 99%
“…Over the past decades, inflammation and a protease/antiprotease imbalance have been the focus of studies that addressed lung destruction following chronic cigarette smoking. More recently, excessive apoptosis of structural alveolar cells has emerged as a major mechanism contributing to the development of lung emphysema, accounting for the unique nature of lung destruction as compared with that with other inflammatory lung diseases (1)(2)(3). The identification of molecular mediators that trigger and integrate lung responses involving inflammation and alveolar cell apoptosis in response to cigarette smoke (CS) exposure offers the potential for development of novel therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Because ceramide is a second messenger molecule that modulates cell apoptosis (13)(14)(15)(16)(17)(18) and oxidative stress (16), others and we have proposed that ceramide upregulation may induce lung epithelial destruction, as presented in the pathogenesis of several lung injury diseases (3,16,19). Recent reports provide a very strong case for cell death (apoptosis) having a major role in lung injury in several pulmonary diseases, such as asthma, bronchitis, and COPD (1,3,5,(20)(21)(22). In simple terms, loss of cells by augmented apoptosis would be expected to be involved, or perhaps initiate, the overall tissue destruction responsible for lung injury (21,22).…”
mentioning
confidence: 99%